Association between psychosis and substance use in Kenya. Findings from the NeuroGAP-Psychosis study - Nguata, Monica; Orwa, James; Kigen, Gabriel; Kamaru, Edith; Emonyi, Wilfred; Kariuki, Symon; Newton, Charles; Ongeri, Linnet; Mwende, Rehema; Gichuru, Stella; Atwoli, Lukoye (Frontiers in Psychiatry, 2024)
Background: Substance use is prevalent among people with mental health issues, and patients with psychosis are more likely to use and misuse substances than the general population. Despite extensive research on substance abuse among the general public in Kenya, there is a scarcity of data comparing substance use among people with and without psychosis. This study investigates the association between psychosis and various substances in Kenya.: This study utilized data from the Neuro-GAP Psychosis Case-Control Study between April 2018 and December 2022. The KEMRI-Wellcome Trust Research Programme conducted the study. They recruited participants from various sites in Kenya, including Kilifi County, Malindi Sub-County, Port Reitz Coast General Provincial Hospitals, and Moi Teaching and Referral Hospital, as well as affiliated sites in Webuye, Kapenguria, Kitale, Kapsabet, and Iten Kakamega. The collected data included sociodemographic information, substance use, and clinical diagnosis. We used summary measures of frequency (percentages) and median (interquartile range) to describe the categorical and continuous data, respectively. The chi-square test was employed to examine the association between categorical variables related to psychosis. Logistic regression models were applied to assess the factors associated with the odds of substance use, considering all relevant sociodemographic variables.We assessed a total of 4,415 cases and 3,940 controls. Except for alcohol consumption (p-value=0.41), all forms of substance use showed statistically significant differences between the case and control groups. Cases had 16% higher odds of using any substance than controls (aOR: 1.16, 95%CI: 1.05-1.28, p=0.005). Moreover, males were 3.95 times more likely to use any substance than females (aOR:3.95;. All the categories of living arrangements were protective against substance use.The findings of this study suggest that psychotic illnesses are associated with an increased likelihood of using various substances. These findings are consistent with those of previous studies; however, it is essential to investigate further the potential for reverse causality between psychosis and substance abuse using genetically informed methods.